Accumulation of Sulfonic Acid Groups Anchored in Covalent Organic Frameworks as an Intrinsic Proton‐Conducting Electrolyte. Issue 1 (7th January 2022) - Zhai, Lipeng; Yao, Yuze; Ma, Baiwei; Hasan, Md. Mahmudul; Han, Yuxi; Mi, Liwei; Nagao, Yuki; Li, Zhongping
Abstract : Front Cover : In article number 2100590 by Liwei Mi, Yuki Nagao, Zhongping Li, and co‐workers, covalent organic frameworks (COFs) with abundant built‐in sulfonic acid groups on the uniform 1D channel are prepared as proton‐conducting electrolytes. The excellent proton conductivity of 1.5 × 10 −2 S cm −1 at 25 ℃ and 95% relative humidity (RH) with binder‐free properties is achieved for the sulfonated COFs, which rank in excellent performance as a proton‐conducting electrolyte.